The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fgene.2020.00700
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Extracellular Vesicles and Their Diverse RNA Contents

Abstract: Cells release nanometer-scale, lipid bilayer-enclosed biomolecular packages (extracellular vesicles; EVs) into their surrounding environment. EVs are hypothesized to be intercellular communication agents that regulate physiological states by transporting biomolecules between near and distant cells. The research community has consistently advocated for the importance of RNA contents in EVs by demonstrating that: (1) EV-related RNA contents can be detected in a liquid biopsy, (2) disease states significantly alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 315 publications
0
141
0
1
Order By: Relevance
“…We have also profiled the RNA of salivary EVs. There has been expansive interest in the diverse RNA content of EVs 63 , including by the Extracellular RNA Communication (ERC) program 64 , for applications in liquid biopsies, as markers in disease states and for cell-free precision medicine diagnostics. EVs are being evaluated as mediators of intercellular communication through molecular transport, offer stable containment of RNA, and can easily be collected for potential diagnostics 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also profiled the RNA of salivary EVs. There has been expansive interest in the diverse RNA content of EVs 63 , including by the Extracellular RNA Communication (ERC) program 64 , for applications in liquid biopsies, as markers in disease states and for cell-free precision medicine diagnostics. EVs are being evaluated as mediators of intercellular communication through molecular transport, offer stable containment of RNA, and can easily be collected for potential diagnostics 63 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been expansive interest in the diverse RNA content of EVs 63 , including by the Extracellular RNA Communication (ERC) program 64 , for applications in liquid biopsies, as markers in disease states and for cell-free precision medicine diagnostics. EVs are being evaluated as mediators of intercellular communication through molecular transport, offer stable containment of RNA, and can easily be collected for potential diagnostics 63 . EVs have been detected and may move across biofluids, with RNAs from bacteria, fungi, and other species having been reported in human plasma and saliva [65][66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis showed that the boar SP-EVs expressed the EVs markers CD63 and CD9 and were free of cell contamination ( Figure 1C ). However, recent study has indicated that ultracentrifugation alone may not be sufficient to isolate clean EVs; an additional purification process such as a density gradient ultracentrifugation made with iodixanol might be applied to remove the aggregates ( 36 ). Although we tried to isolate boar SP-EVs using membrane-based affinity binding and precipitation, methods that are commonly used to isolate EVs from bioliquids, the yield was too small for TEM analysis (data are not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional evidence has accumulated that ExMVs play a role in the spread of certain viruses and prions [ 2 , 27 , 28 ]. Currently under investigation is the possibility that ExMV molecular signature and content will be important tools in diagnostics as part of so-called liquid biopsies [ 20 , 29 ].…”
Section: Introductionmentioning
confidence: 99%